Early parameter to detect the resolution of pediatric diabetic ketoacidosis - Liu, Yi-Hsuan; Su, Ya-Ting; Lin, Jainn-Jim; Chan, Oi-Wa; Yen, Chen-Wei; Lee, En-Pei (Frontiers in Pediatrics, 2025)
ObjectiveThe present study aimed to analyze the incidence of hyperchloremia and compare the time to reach DKA resolution with different parameters.MethodsA chart review of patients diagnosed with DKA and aged <18 years was conducted. DKA was defined as serum glucose ≧200 mg/dl, venous pH (vpH) <7.30, serum bicarbonate <15 mmol/L, and presence of ketonemia, or ketonuria. Electrolytes and blood gases were recorded at 6-h intervals after treatment initiation.ResultsOverall, 84 patients were admitted because of DKA. The initial biomedical parameters in the emergency department were as follows: median glucose, 497 mg/dl; vpH, 7.1; serum HCO3, 6.6 mmol/L; anion gap (AG), 24.7 mmol/L; and ketone, 5.7 mmol/L. After treatment, the incidence of hyperchloremia increased progressively from 15.4% at treatment initiation to 80% at 18 h. The median time to resolution defined by AG ≦12 mmol/L was 12 h, which was significantly faster than the recovery of vpH ≧7.3 (median time, 17 h) and HCO3 >15 mmol/L (median time, 18 h). Approximately 63 (75%) patients reached the endpoints of AG ≦12 mmol/L prior, 14 (16.6%) patients reached the endpoints of vpH ≧7.3 prior, 7 (8.4%) patients reached the endpoints of HCO3 >15 mmol/L prior.ConclusionsHyperchloremic metabolic acidosis (HMA) was a common entity in pediatric DKA following treatment. The median time of AG ≦ 12 mmol/L was approximately 12 h and was the parameter that can identify DKA resolution at a faster rate, i.e., approximately 5, and 6 h faster than the normalization of vpH and HCO3, respectively. Future studies were warranted to use AG ≦12 mmol/L as the endpoint of DKA treatment and check if the treatment course and incidence of HMA could be reduced.